Transcriptomic Characterization of a Chicken Embryo Model Infected With Duck Hepatitis A Virus Type 1 - Xie, Jinyan; Zeng, Qiurui; Wang, Mingshu; Ou, Xumin; Ma, Yunchao; Cheng, Anchun; Zhao, Xin-Xin; Liu, Mafeng; Zhu, Dekang; Chen, Shun; Jia, Renyong; Yang, Qiao; et al. (Frontiers in Immunology, 2018)
Duck hepatitis A virus type 1 (DHAV-1) is one of the most common and lethal pathogens in young ducklings. Live attenuated DHAV vaccine (CH60 strain) developed by passaging in chicken embryos provided effective immune protection for ducklings. However, the accurate mechanism for such adaption in chicken embryos is not fully revealed. Here, we utilize RNA-sequencing to perform global transcriptional analysis of DHAV-1-innoculated embryonated livers along with histopathological and ultrastructural analysis. This study revealed that infection with DHAV-1 strain CH60 is associated with enhanced type I and II interferon responses, activated innate immune responses, elevated levels of suppressor of cytokine signaling 1 and 3 (SOCS1 and SOCS3) accompanied with abnormalities in multiple metabolic pathways. Excessive inflammatory and innate immune responses induced by the CH60 strain are related to severe liver damage. Our study presents a comprehensive characterization of the transcriptome of chicken embryos infected with DHAV-CH60 and provides insight for in-depth exploration of viral adaption and virus-host interactions.